The economic benefit of timely, adequate, and adherence to Parkinson's disease treatment: the Value of Treatment Project 2. (8th November 2020) - Dodel, R.; Tinelli, M.; Deuschl, G.; Petersen, G.; Oertel, W.; Ahmerkamp‐Böhme, J.
Abstract : Background: Parkinson's disease (PD) is a chronic progressive neurological disorder with a high psychosocial and economic burden. As part of the European Brain Council (EBC)‐led Value of Treatment project, this study aimed to capture the economic benefit of timely, adequate, and adherence to PD treatment. Methods: The EBC Value of Treatment Initiative combined different stakeholders to identify unmet needs in the patients' journey according to Rotterdam methodology. The economic evaluation focused on three major topics identified as major gaps: start of treatment; best treatment for advanced disease; and adherence to treatment. Two separate healthcare systems (Germany and the UK) were chosen. Cost‐effectiveness was determined by using decision‐analytical modelling approaches. Effectiveness was expressed as quality‐adjusted life‐years (QALYs) gained and incremental cost‐effectiveness ratio (ICER). Results: Treatment intervention in PD was found to be cost‐effective regardless of the initial health state of the patient receiving the treatment. Cost savings were between ‐€1000 and −€5400 with 0.10 QALY gain and ‐€1800 and ‐€7600 with 0.10 QALY gain for Germany and the UK, respectively. Treatment remains cost‐effective within the National Institute for Health and Care Excellence thresholds. Availability of adequate treatment to more patients was also found to be cost‐effective, with an ICER of €15, 000–€32, 600 across country settings. Achieving the target adherence to treatment would generate cost‐savings of €239, 000–€576, 000 (Germany) and €917, 000–€2, 980.000 (UK) for every 1, 000 patients treated adequately. Conclusions: The analyses confirmed that timely, adequate, and adherence to PD treatment will not only improve care of the patients but is also cost‐effective across healthcare systems. Further studies with a distinct identification of gaps in care are necessary to develop better and affordable care. Abstract : As part of the European Brain Council (EBC)‐led Value of Treatment Project, this study aimed to capture the economic benefit of a timely, adequate, and adherence to PD treatment. The economic analyses confirmed the benefits of timely, adequate, and adherence to PD treatment. It will not only improve care of the patients but is also cost‐effective (when addressing gap 2: providing adequate treatment for advanced PD) and cost‐saving (when addressing gaps 1 and 3: providing early/timely treatment and improving the rates of adherence to optimal care) across healthcare systems.